Statistical domain wall roughness analysis through correlations - Domenichini, Pablo Exequiel (2023)
The geometry and morphology of magnetic domain walls (DWs) are closely related to their dynamics when driven by external forces. Under some reliable approximations DWs can be considered self-affine interfaces, so universal laws govern their behavior. On the other hand, large-scale DW structure has been less explored so far. Recently, it has been shown that bubble-like magnetic domains can be strongly deformed on a large scale by applying alternating (ac) magnetic field pulses. In the present paper, we conduct a comprehensive analysis of DW structure at both small and large length scales in bubble-like domains present in ferromagnetic thin films with perpendicular anisotropy, focusing on its initial evolution under the application of ac magnetic pulses. Results obtained from the widely used roughness correlation function B(r) and its corresponding structure factor, are consistent with those obtained from the spatial autocorrelation function of DW fluctuations. Whereas the roughness exponent slightly increases during the ac evolution, a strong deformation is observed at a large scale, where a striking periodicity (statistically speaking) is observed. This period is probably determined by the boundary conditions and a characteristic intrinsic length.